Pengawetan Telur Ayam dengan Antimikroba Alami - May Dwi Yuri Santoso (Universitas Mulawarman, 2020)
Sragen is one of the regencies in Central Java Province, located on the border between Central Java and East Java. The natural condition of Sragen is still beautiful because of the large amount of open land. The majority of the livelihoods of Sragen residents are farmers. One of the agricultural fields is raising laying hens in Sambirejo, Masaran and Gondang Districts. This laying hen breeder supplies chicken egg needs in Sragen Regency. The population of Sragen in general still relies on nutritional intake of sources of animal nutrition, one of which comes from chicken eggs. Chicken eggs in room temperature storage can only last a maximum of 14 days. This can be caused by the presence of pathogenic bacteria that attach to the skin or shell of the chicken egg causing it to accelerate the process of decaying chicken eggs. In order for chicken eggs to be more durable, an alternative method of preserving chicken eggs is needed with natural anti microbes. Natural anti-microbial can be obtained from pepaya leaves. To the knowledge of the author, this alternative method has never been done so that it can become a creativity and innovation. The rationale for this method is that natural anti microbial from pepaya leaves will kill or inhibit the growth of pathogenic bacteria so that chicken eggs will become more durable and not rot quickly. The results of the research we did showed that chicken eggs can be preserved with natural anti-microbial for 28 days.